Exact and fast calculation of the X‐ray pair distribution function. Issue 3 (13th May 2020) - Neder, Reinhard B.; Proffen, Thomas
Abstract : A fast and exact algorithm to calculate the powder pair distribution function (PDF) for the case of periodic structures is presented. The algorithm especially improves X‐ray and electron PDF calculations, and the handling of instrumental resolution functions. Abstract : A fast and exact algorithm to calculate the powder pair distribution function (PDF) for the case of periodic structures is presented. The new algorithm calculates the PDF by a detour via reciprocal space. The calculated normalized total powder diffraction pattern is transferred into the PDF via the sine Fourier transform. The calculation of the PDF via the powder pattern avoids the conventional simplification of X‐ray and electron atomic form factors. It is thus exact for these types of radiation, as is the conventional calculation for the case of neutron diffraction. The new algorithm further improves the calculation speed. Additional advantages are the improved detection of errors in the primary data, the handling of preferred orientation, the ease of treatment of magnetic scattering and a large improvement to accommodate more complex instrumental resolution functions.